Candida vascular complication in a liver transplant recipient due to yeast contamination of preservation solution. Issue 5 (1st July 2014) - Levesque, E.; Suet, G.; Merle, J.C.; Compagnon, P.; Amathieu, R.; Feray, C.; Botterel, F.; Foulet, F.; Azoulay, D.; Dhonneur, G.
Abstract Infections remain a major cause of morbidity and mortality after liver transplantation. One possible cause of infection is preservation fluid contamination. Donor‐derived pathogens, such as Candida albicans, have occasionally produced life‐threatening complications in organ recipients, already described in renal transplantation. In the present case, we report the loss of a liver graft secondary to vascular complications because of C. albicans found in the preservation fluid. Our case report raises the question of implementing procedures, similar to those in renal transplantation, including early antifungal treatment and repeated radiological monitoring for the prevention and detection of vascular complications.